Emergence of the E484K Mutation in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Lineage B.1.1.345 in Upstate New York. (4th June 2021) - Lesho, Emil; Corey, Brendan; Lebreton, Francois; Ong, Ana C; Swierczewski, Brett E; Bennett, Jason W; Walsh, Edward E; McGann, Patrick
Abstract: A severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) B.1.1.345 variant carrying the E484K mutation was detected in 4 patients with no apparent epidemiological association from a hospital network in upstate New York. Subsequent analysis identified an additional 11 B.1.1.345 variants from this region between December 2020 and February 2021.